Qualidade fisiológica de sementes de cajueiro, clone CCP-76, em função da forma de colheita e do tempo de armazenamento - Vieira, Francisco Elvis Ramos (Universidade Federal Rural do Semi-Árido, 2011)
This work has as objective to evaluate the physiological quality of cashew seeds. Utilizing seeds physiologically ripe picked off from the crown of the plants and the seeds fallen under their crowns during a period of 30 days after the harvest from the crowns. The seeds from those two harvests were stored in room temperature in laboratory. The seeds were obtained during the harvest time of 2009 from 140 grown cashew plants from the CCP-76 clone, from an orchard in full production at the Maracaí Settlement, located in the Rural Area in the city of Ipiranga do Piauí. The experimental delineating was entirely randomized in a factorial scheme (7x2) with four repetitions with 25 seeds per treatment. The first scheme was constituted of the seed storage time (Zero, 30, 60, 90, 120, 150, and 180 days) and the second one of seed collection kind (plant and soil). The analyses were carried out in the Seed Analysis Laboratory and in the Green House of the Vegetable Science Department at Universidade Federal Rural do Semi-Árido (UFERSA), in Mossoró-RN, from September, 2009 to July, 2010. The germination percentage and the germination velocity index were evaluated in laboratory. At the green house, the emergency percentage, emergence velocity index, plant height, stalk diameter, leaf number, leaf area, and upper part dry mass. The storage affected negatively the seed vigor, but the seeds collected from the plants showed better physiological features, providing a greater emergence velocity index, stalk diameter, leaf number, plant height, leaf area, and upper part dry mass.
Physiological quality of cashew seeds, CCP-76 clone, in function of the harvest form and storage time
Keywords: Anacardium occidentale L; Vigor; Seeds; Germination; Anacardium occidentale L; Vigor; Sementes; Germinação; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA